Leonidov in the Crimea, 1936–1938. Part 4 - Zavadovsky, Petr (project baikal, 2025)
The fourth article of the cycle devoted to I. I. Leonidov’s projects for the southern coast of the Crimea continues to consider the architecture of the buildings of the central Yalta embankment, in particular, the resort hotels and park pavilions. An attempt is being made to reconstruct them on the basis of preserved materials.
Keywords: I. I. Leonidov; the southern coast of the Crimea; Yalta; graphic reconstruction; postconstructivism; late constructivism